Real-Time Bird's Eye Surround View System: An Embedded Perspective. Issue 10 (24th August 2021) - Al-Hami, Mo'taz; Casas, Raul; El Salhi, Subhieh; Awwad, Sari; Hussein, Fairouz
ABSTRACT: Bird's-eye surround view is a new type of Advanced Driv er Assistance System (ADASs) that provides drivers with a real-time 360 ∘ top-down view of their vehicle. This paper presents an architecture for a surround view system based on a Tensilica Vision P5 embedded DSP. Fish-eye cameras mounted on each side of a vehicle are employed in the proposed model. The cameras are able to cover the entire view around the vehicle with overlapping areas between neighboring cameras. We use a morphing approach for joint lens and perspective correction of each view. For stitching frames from different cameras, we assume a fixed geometry which permits off-line calculation of frame transformations, thereby reducing the real-time processing load. To further reduce computational complexity, we employ lookup-tables in the view morphing and blending phases. The Vision P5 core combines the four frames with XGA resolution into a single XGA surround view at 30FPS.